21ST CENTURY SKILLS TRANSFORMATION THROUGH KARAWO PRODUCTS DIVERSIFICATION ON CREATIVE ECONOMY TOWARDS UMKM KARAWO EMPOWERMENT - Danial, Haris; Ismail, Yulinda L; Padiku, Indhitya R (Universitas Pahlawan Tuanku Tambusai, 2024)
This program aims to increase the capacity of business actors in facing the challenges of the modern market through innovation of Karawo products, which are typical crafts of Gorontalo. Through this empowerment program, Karawo MSME are encouraged to be more innovative in creating new products that are varied and in accordance with modern market demand. The process of diversifying products based on the creative economy includes creating more diverse Karawo designs and utilizing technology to expand the market. With the help of digital skills, MSME actors can market Karawo products more widely through online platforms, strengthen branding, and expand consumer reach. The development of creativity and innovation not only increases competitiveness, but also enriches local culture with modern Karawo designs without eliminating traditional elements. This empowerment has resulted in increased income and strengthened economic capacity at the community level. The results of this service show an increase in the innovation and creativity capabilities of Karawo MSME. In addition, better digital literacy helps business actors utilize e-commerce platforms and social media to market their products more widely, both in local and national markets. Overall, the transformation of 21st century skills through the diversification of Karawo products based on the creative economy has had a positive impact on the sustainability of MSMEs in Dunggala Village, creating new economic opportunities, and strengthening local cultural identity in facing the challenges of globalization.